A Buddhist Doctrine of Experience: A New Translation and Interpretation of the Works of Vasubandhu the Yogacarin - Mundadan, A M (Journal of Dharma, 1984)
Thomas A. Kochumuttom A Buddhist Doctrine of Experience (A New Translation and Interpretation of the Works of Vasubandhu the Yogacarin) Delhi: Motilal Banarsidass, 1982, pp xxiv + 287, Rs. 100/-